Functional connectivity analysis using fNIRS in healthy subjects during prolonged simulated driving - Xu, Liwei; Wang, Bitian; Xu, Gongcheng; Wang, Wei; Liu, Zhian; Li, Zengyong (Neuroscience letters, 2017)
•Simulator combined semi-immersive virtual reality (VR) technology and fNIRS were designed to detect brain activities.•Focus on functional connectivity (FC) between brain regions, not merely variations in concentration of oxyhemoglobin.•Wavelet coherence and wavelet phase coherence reveal the strength and synchronization of FC, respectively.•FC among brain regions are closely related to fatigue caused by prolonged driving. Noninvasive and accurate assessment of driving fatigue in relation to brain activity during long-term driving can contribute to traffic safety and accident prevention. This study evaluated functional connectivity (FC) in relevant brain regions. Synergistic mechanisms in different brain regions were detected by a novel simulator, which combined semi-immersive virtual reality technology and functional near-infrared spectroscopy. Each subject was instructed to complete driving tasks coupled with a mental calculation task. Wavelet coherence (WCO) and wavelet phase coherence (WPCO) were calculated and assessed in frequency intervals (I) 0.6–2 and (II) 0.145–0.6Hz as global connectivity measures; (III) 0.052–0.145, (IV) 0.021–0.052, (V) 0.0095–0.021 and (VI) 0.005–0.0095Hz as FC. WCO and WPCO revealed the strength and synchronization of cerebral connectivity, respectively. Significantly low WCO levels were found in intervals I and III in prefrontal cortex (PFC) and IV in motor cortex (MC) at the end of the driving task. Furthermore, significantly low WPCO were found in intervals I, and III in PFC and interval IV in MC. Experimental findings suggested that progressive mental fatigue adversely influences the cognitive function in the PFC and the cooperative mechanism between the PFC and MC.